A late 2nd/early 1st millennium BC interaction arc between Mainland Southeast Asia and Southwest China: Archaeometallurgical data from Hebosuo and Shangxihe, Yunnan. (July 2022) - Pryce, T.O.; Lam, Wengcheong; Cadet, Mélissa; Jiang, Zhilong; Yang, Wei; Yao, Alice
Abstract: In this paper we use archaeometallurgical data from the Yunnanese Bronze Age sites of Hebosuo and Shangxihi, to examine the nature of early exchange networks within Yunnan, across southern China and into Mainland Southeast Asia (MSEA). Traditional perspectives on relations between China and MSEA were viewed from a Core-Periphery (C–P) perspective, derived from World Systems Theory (WST) but this area, though now divided by national borders, has shared ecological and cultural characteristics that allow its definition as the Southeast Asian Massif (SAM). The fourteen analysed samples were all unleaded copper or bronze, mostly as-cast and with some annealing. Their lead isotope signatures did not group at site level but showed broad consistency with the other, limited, signatures available from Yunnan, Sichuan and Guangxi. Critically, comparison with MSEA signatures revealed good isotopic consistency with key Bronze Age sites in Thailand, Myanmar and Vietnam, active within tight timeframes, and mostly lying on or near the path of major river systems that find their source in or via Yunnan. The picture we propose, based on current data, is one of a complex network of autochthonous SAM societies interacting at short (ca. 50 km), medium (ca. 300 km) and long (ca. 800–1600 km) ranges over mountainous and forested terrain. Highlights: Yunnan and Mainland Southeast Asia have recently aligned Bronze Age chronologies. 14 copper-base artefacts from early 1st mill. BC Hebosuo and Shangxihi were analysed. 8 were unleaded copper and 6 were unleaded copper.11 as-cast, 2 annealed & 1 corroded. Lead isotope ratios did not cluster intrasite but were consistent with southern China. Consistency with selected Mainland Southeast Asian signatures suggests radial network.